2008
DOI: 10.1196/annals.1405.017
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐specific Apheresis of Pathogenic Autoantibodies from Myasthenia Gravis Sera

Abstract: Myasthenia gravis (MG) is usually caused by autoantibodies against muscle nicotinic acetylcholine receptor (AChR), which is composed of five subunits (alpha(2)betagammadelta or alpha(2)betaepsilondelta). Current treatments, including plasmapheresis, are nonspecific, causing several side effects. We aim to develop an antigen-specific alternative to plasmapheresis, since the latter removes indispensable plasma components in addition to anti-AChR antibodies. We are developing a method for the selective depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In this report, we are applying our extensive expertise on AChRimmunoadsorption for the development of a specific extracorporeal treatment (Psaridi-Linardaki et al, 2005;Tzartos et al, 2008;Zisimopoulou et al, 2008a;Zisimopoulou et al, 2008b;Lazaridis et al, 2012) in order to follow a similar approach for MuSK-MG. Specifically, we aimed to deplete MuSK antibodies from patients' sera using the immobilized MuSK-ECDs as immunoadsorbents.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we are applying our extensive expertise on AChRimmunoadsorption for the development of a specific extracorporeal treatment (Psaridi-Linardaki et al, 2005;Tzartos et al, 2008;Zisimopoulou et al, 2008a;Zisimopoulou et al, 2008b;Lazaridis et al, 2012) in order to follow a similar approach for MuSK-MG. Specifically, we aimed to deplete MuSK antibodies from patients' sera using the immobilized MuSK-ECDs as immunoadsorbents.…”
Section: Discussionmentioning
confidence: 99%
“…Their relevance in human heart disease and failure, however, still need to be substantiated Fu, M., 2008) although preliminary clinical data suggest that the presence of certain cardiac aabs clearly worsens the prognosis of patients with idiopathic DCM (Störk et al, 2006). Therapeutic strategies known from other autoimmune disorders, such as application of peptide-ligands (for multiple sclerosis (Warren et al, 2006)) or immunoadsorption of disease-causing aabs (for myasthenia gravis (Tzartos et al, 2008)) might thus also offer treatment options for a variety of human cardiac disorders. In this regard, recent in vitro experiments with functionally active receptor-aabs isolated from a smaller number of DCM-patients indicate, that aab-induced adrenoceptor activation might be abrogated by incubation with epitope-mimicking peptides (Nikolaev et al, 2007;Jahns et al 2010).…”
Section: Future Perspectives and Therapeutic Implicationsmentioning
confidence: 99%
“…Such a removal is achieved by "immunoadsorbent" columns consisting of the ECDs of all human muscle AChR subunits. They showed that the antibody-depleted sera lost the ability to passively induce EAMG in rats suggesting that ECD-mediated immunoadsorption could be used as an efficient, antigen-specific treatment for MG [49].…”
Section: Apheresis Of Pathogenic Anti-achr Antibodiesmentioning
confidence: 99%